MECHANICAL PROPERTIES OF QUENCH-HARDENED, MARTEMPERED AND TEMPERED ASTM A 128 GRADE B-4 STEEL (Journal of Science and Technology, 2016)
This investigation is conducted to assess the influence of some heat treatment procedures on the structure and mechanical properties of cast ASTM A grade B-4 steel to which formation of grain boundary carbides have been a major problem. Some cast ASTM A grade B-4 steel samples were quench-hardened, martempered and tempered. The as-cast and heat-treated samples were thereafter tested for tensile strength, yield strength, impact strength, ductility and hardness. Some of the samples were also prepared for metallographic examination and their microstructures were studied. It was observed that in all cases, the microstructures were mainly austenite matrix with or without carbides at the grain boundaries and in the austenitic grains depending on the heat-treatment adopted. The measured mechanical properties varied and were greatly dependent on the presence or absence of carbides either at the grain boundaries or at both the grain boundaries and in the grains of austenite matrix. Two of the heat treatment procedures were found to be appropriate as post-casting processes suitable for ASTM A 128 grade B-4 steel components designed to function under a condition in which impact strength and hardness are simultaneously required.